Web-based Information System for Climbing Equipment Rental (Case Study of Camp 2 Shop): Sistem Informasi Penyewaan Alat Hiking Berbasis Web (Studi Kasus Toko Camp 2) - Malna, Intan Afriza; Findawati, Yulian (Universitas Muhammadiyah Sidoarjo, 2023)
The business of renting hiking equipment is currently very much loved by entrepreneurs. Due to the fact that the content business generates a lot of rupiah coffers, nowadays many young people are channeling their hobbies to mountain climbing. Regardless of age, there are also many ambitious fathers who take the time to climb. No wonder hiking equipment rentals are selling well at this time.Unfortunately, the rental of hiking equipment is still traditional, namely by coming to the store and choosing the items to be rented, with a system like this it is likely that the items to be rented are empty or are being rented by other tenants. This is quite detrimental to customers who have come all the way and hope that the item they are looking for is there. Not only customers who are harmed here, shop owners will also lose many customers.Therefore, a web-based information system is needed that can be accessed by potential customers, with this information system it is hoped that it can assist customers in renting hiking equipment without manual processes.